Body composition and bone status of children born to mothers with type 1 diabetes mellitus. Issue 4 (24th March 2010) - Mughal, M Z; Eelloo, J; Roberts, S A; Maresh, M; Ward, K A; Ashby, R; Sibley, C P; Adams, J E
Abstract : Background: Altered growth, body composition and abnormalities of skeletal mineralisation have been reported in offspring of mothers with type 1 and type 2 diabetes mellitus. Aims: The authors hypothesised that children born to mothers with type 1 diabetes mellitus (CDM) would be taller, have higher body mass index (BMI), greater fat mass, thicker diaphyseal bone cortices and reduced trabecular bone mineral density (BMD), as compared to those born to non-diabetic mothers. Methods: Anthropometric, body composition and bone parameters were assessed using dual-energy x-ray absorptiometry (DXA) and peripheral quantitative CT in 67 white Caucasian CDM (35 boys; age 5–18 years) and in 246 (121 boys) age-matched controls. Results: CDM were taller (p<0.0001), heavier (p<0.0001) and had higher BMI (p=0.02), and had 32% more total body fat mass and 7.5% more total body lean mass than controls. At the total body and lumbar spine (L1–L4) sites, CDM had significantly higher bone area and bone mineral content compared with controls. However, areal BMD at both these sites and lumbar spine bone mineral apparent density were not significantly different in the two groups, indicating that CDM have bigger bones compared with controls but their mineral content per unit area or volume is not substantially different. The distal radial trabecular and total volumetric BMD in CDM was not demonstrably different from controls. At the mid-radius, both periosteal (2.4%; p=0.03) and endosteal circumferences (5.7%; p=0.02) were bigger in CDM compared with controls. Conclusion: The authors speculate that the intrauterine diabetic environment is associated with an increase in linear growth, adiposity and larger bone dimensions during childhood and adolescence.